2015
DOI: 10.47552/ijam.v6i1.515
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Shilajatu in Madhumeha

Abstract: The incidence of diabetes mellitus is increasing rapidly because of changes in dietetic habits and life style. Continuous research is being done by scientists of various fields in order to achieve an effective cure of the disease. A great deal of work has also been done by Ayurvedic research scholars on various herbal and mineral drugs to find an effective treatment for Prameha. Shilajatu is one such drug which has been described for the management of Prameha in Ayurveda texts. The present study was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…[16] Shilajatu inturn helps in reduction of lipid and sugar from the gut. [17] A double-blind trial of Antarkar et al (1980) conducted on acute viral hepatitis with Arogyavardhini had showed significant hepatoprotective effects by reducing inflammation of spleen, liver, bladder, kidneys, uterus and intestine. [18] In the present study Arogyavardhini vati was prepared according to the Ayurvedic classics and was subjected to physicochemical analysis and standardization as per the Ayurvedic Formulary of India.…”
Section: Pharmacological Action Of Arogyavardhani Vatimentioning
confidence: 99%
“…[16] Shilajatu inturn helps in reduction of lipid and sugar from the gut. [17] A double-blind trial of Antarkar et al (1980) conducted on acute viral hepatitis with Arogyavardhini had showed significant hepatoprotective effects by reducing inflammation of spleen, liver, bladder, kidneys, uterus and intestine. [18] In the present study Arogyavardhini vati was prepared according to the Ayurvedic classics and was subjected to physicochemical analysis and standardization as per the Ayurvedic Formulary of India.…”
Section: Pharmacological Action Of Arogyavardhani Vatimentioning
confidence: 99%